The utilization of nanoparticles to modify surface properties in acidification processes - AlAmeen, Ahmed; Almahdawi, Faleh; Azin, Reza; Suramairy, Ramyar (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Stimulation plays a crucial role in the oil and gas industry, particularly in the acidizing process. Thus, the development of acidification processes is essential for improving the productivity index and enhancing the physical properties of reservoirs. This research investigates the effect of Tin oxide (SnO2) and Titanium dioxide (TiO2) nanomaterials on the surface properties in acidic media of hydrochloric acid (HCl) at various acid and nanomaterials concentrations, as well as their impact on the wettability of carbonate rocks. To achieve this, surface tension, contact angle, and zeta-potential were measured using various instruments. The findings show that SnO2 and TiO2, at a concentration of 1000 ppm, significantly reduce surface tension to 34.69 and 43.44 mN/m, respectively, while maintaining stability with zeta potential values up to 51.27 and 49.17 mV, respectively. These results exceed the generally accepted stability threshold of around ±30 mV, indicating a strong electrostatic repulsion that prevents agglomeration and ensures prolonged suspension stability. Additionally, the findings show a substantial decrease in contact angles, from 95.17° to 16.32° with SnO2 and from 98.48° to 25.26° with TiO2. This shift indicates a transition from non-wetting to a more wetting condition, which is crucial because it reflects an increased affinity of the acid solution for the carbonate rock surfaces. This results in promoting better acid distribution and enhancing rock dissolution. In conclusion, both SnO2 and TiO2 reveal excellent performance as surfactants in the stimulation process, presenting substantial benefits for the acidizing process in the oil and gas industry.